Abu Zaid Al-Balkhi's Psychotherapy from the Perspective of the Qur'an - Sholekhawati, Sholekhawati (CV. Publikasi Indonesia, 2025)
This study aims to explore Abu Zaid Al-Balkhi's psychotherapy in the perspective of Qur'anic values relevant to mental health. The background of this research focuses on the urgency of mental health which has a significant impact on the quality of life of individuals. The research method used a combined quantitative and qualitative approach with an in-depth literature study of Al-Balkhi's main work, Mashâlih al-Abdân wa al-Anfus. The results showed that the Qur'an provides a description of the condition of the human soul, both in a normal state and mental disorders such as fear, evil thoughts, anxiety, and despair. The psychotherapeutic solutions offered by Al-Balkhi include strengthening faith, worship, and ethics integrated with Qur'anic values. The research conclusion confirms that Al-Balkhi's concept of psychotherapy is relevant to current mental health needs and provides practical guidance in maintaining physical, mental, spiritual and social well-being. This psychotherapy can contribute to the development of productive human resources through a holistic and humanist approach.